A comparison of 16S rRNA-gene and 16S rRNA-transcript derived microbial communities in bulk and rhizosphere soils - Ceretto, Alessandra; Weinig, Cynthia (Frontiers in Microbiology, 2025)
Root exudates in a plant’s rhizosphere alters microbial community membership and activity, which can in turn alter a plant’s health and fitness. In this study we characterized bacterial community composition, using 16S rRNA-gene (DNA) sequencing to define total community membership and 16S rRNA-transcripts (RNA) to define protein synthesis potential (PSP) as a proxy of microbial activity in both rhizosphere and bulk soils of a Wyoming native plant Boechera stricta. Using PSP rather than total microbial membership reveals fine-scale differences in genera between the rhizosphere and control soil communities. This study found DNA community analysis alone disproportionately increased the importance of Saccharibacteria and Gemmatimonadetes phyla in the overall soil community profile, and underestimated the importance of several known root associates (Comamonadaceae, Rhizobacter, and Variovorax), which had elevated PSP in the rhizosphere soil. Thus, the use of DNA-vs. RNA-based community characterization reveals that community composition (DNA) may not completely capture community activity (RNA). Analysis of the PSP community profile also indicated elevated levels of proteins associated with carbohydrate and amino acid metabolism in the rhizosphere-associated bacteria, which may shed light on potential mechanisms by which root exudates shape the rhizosphere soil community.